Product⋎service system configuration: a generic knowledge-based model for commercial offers. Issue 4 (16th February 2021) - Guillon, Delphine; Ayachi, Rania; Vareilles, Élise; Aldanondo, Michel; Villeneuve, Éric; Merlo, Christophe
Abstract : At a time when modes of consumption are rapidly evolving, consumer attitudes and expectations are changing. Today, customers want more and more products and services that can be customised to their needs. Furthermore, they are more willing to pay for usage of a product rather than ownership. On the other hand, companies are adding more and more services to the products they are bringing to market in order to create added value and differentiate themselves from their competitors. To adapt to these new market trends, companies now have to offer their customers a more sophisticated catalog of solutions, in both product and services, including all conceivable combinations of the two. The aim of this article is to propose a generic knowledge-based model, dedicated to commercial offer configuration which is able to cope with the whole variety of solutions a company can deliver. To our knowledge, although some works on product configuration, service and product-service system configuration exist, none of them is generic enough to support product, service and product-service configuration at the same time when defining commercial offers. In this article, after giving a state-of-the-art assessment of product and service configurations, the need for a generic model able to cover the whole range and diversity of commercial offers is established, a knowledge-based model is defined and its relevance is demonstrated on seven use-cases coming from secondary and tertiary sector companies.